Food and nutrient intake of adolescent women in Medellin, Colombia (2023)
ABSTRACT: Nutritional imbalance in adolescent girls causes alterations in health, reproductive cycles, and fetal outcomes of future generations. To evaluate the dietary pattern and prevalence of inadequate nutrient intake, a 24-hour multi-step food recall was carried out among 793 adolescent women (14–20 years old) from Medellin, Colombia. Their dietary pattern was characterized by lower than recommended intakes of fruits and vegetables (CRI 0.4, AMD 0.2), dairy (CRI 0.5, AMD 0.2), and proteins (CRI 0.8, AMD 0.3), while starches (CRI 1.2, AMD 0.4), fats (CRI 1.1, AMD 0.6), and sugars (CRI 1.0, AMD 0.5) were at similar or higher levels than recommendations. A high risk of deficiency was found in the usual intake of energy (53.0%), protein (39.8%), calcium (98.9%), folates (85.7%), iron (74.4%), thiamine (44.3%), vitamin C (31.3%), zinc (28.3%), vitamin A (23.4%), cyanocobalamin (17.3%), and pyridoxine (10.9%). A low risk of deficiency was noted in usual fiber intake (0.5%), and a higher than recommended intake was noted in saturated fat (100.0%) and simple carbohydrates (68.8%). Anecdotally, a large proportion of respondents saw decreases in their food consumption during the COVID-19 pandemic. These results suggest an urgent need for nutrition education programs to emphasize the importance of adequate nutrition among adolescent women.